Islamic Boarding School Curriculum Management in Forming the Character of Santri at Assuniyah Kencong Islamic Boarding School for the 2019/2020 Academic Year - Zawawi, Muhammad Ilmil (IKAMAS: Manajemen Pendidikan Islam, 2023)
The curriculum is one of the factors that plays an important role in the education system in Islamic boarding schools. This is because the curriculum is a tool used to achieve the goals of education as well as guidelines when implementing learning activities at all levels of education. This study uses a qualitative method. The data sources used are primary and secondary. Data collection techniques used are involved observation, in-depth interviews and documentation. Data analysis using an interactive model. Results: 1) Islamic boarding school curriculum planning obtains results regarding programs for activities to be carried out, strategies in learning and sources of funding to be used. 2) Implementation of the Curriculum is carried out by all students who live in the Islamic Boarding School. 3) Curriculum Evaluation is carried out once a month and every semester in order to be able to carry out an assessment on the manaqib reading test, in order to find out the character development of the students